BOLSHEVIK PROPAGANDA IN JOHN REED’S "TEN DAYS THAT SHOOK THE WORLD" - Trbić, Aleksandar (Politeia, 2026)
The aim of this paper is to give an insight into political propaganda that was used by bolsheviks in the time of October Revolution, as well as the ways it was used during ten days that John Reed wrote about in his work. After introduction, which provides definitions of concept and types of political propaganda, some of the key events in the life of John Reed are presented. This section is followed by an  analysis of key aspects of bolshevik political propaganda, along with techniques of propaganda used and its use in terms which Reed described. The author of this paper has especially analyzed propaganda used in the press, with a review of slogans, proclamations, posters, and public speeches.
Keywords: Political propaganda; Bolsheviks; October Revolution; John Reed; propaganda techniques; press; political communication